2006
DOI: 10.1162/glep.2006.6.1.76
|View full text |Cite
|
Sign up to set email alerts
|

The Rearguard of Modernity: Environmental Skepticism as a Struggle of Citizenship

Abstract: Environmental skepticism denies the reality and importance of mainstream global environmental problems. However, its most important challenges are in its civic claims which receive much less attention. These civic claims defend the basis of ethical authority of the dominant social paradigm. The article explains how political values determine what skeptics count as a problem. One such value described is "deep anthropocentrism," or the attempt to split human society from non-human nature and reject ecology as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
0
43
0
1
Order By: Relevance
“…On the other hand, conservative think tanks and the Republican Party have regularly disparaged mainstream scientists and the pronouncements of the scientific community's most prestigious bodies, while promoting the largely debunked claims of a handful of climate change contrarians (McCright and Dunlap 2003; Lahsen 2005; Demeritt 2006). This conflict reflects a deeper division between those who levy critiques of the industrial capitalist order and those who defend the economic system from such challenges (Jacques 2006; McCright and Dunlap 2010; Oreskes and Conway 2010). Our results provide strong evidence that the long‐term divide over global warming between elites and organizations on the Left and the Right has in recent years emerged within the general public as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, conservative think tanks and the Republican Party have regularly disparaged mainstream scientists and the pronouncements of the scientific community's most prestigious bodies, while promoting the largely debunked claims of a handful of climate change contrarians (McCright and Dunlap 2003; Lahsen 2005; Demeritt 2006). This conflict reflects a deeper division between those who levy critiques of the industrial capitalist order and those who defend the economic system from such challenges (Jacques 2006; McCright and Dunlap 2010; Oreskes and Conway 2010). Our results provide strong evidence that the long‐term divide over global warming between elites and organizations on the Left and the Right has in recent years emerged within the general public as well.…”
Section: Resultsmentioning
confidence: 99%
“…Political psychologists find that conservatives are more likely to express system justification tendencies, while liberals are more amenable to critiques of the established order (e.g., Feygina, Jost, and Goldsmith 2010). Compared with local environmental problems such as water and air pollution, global environmental problems like climate change pose a stronger challenge to conservatives' faith in unfettered industrial capitalism as the desirable and inevitable path to progress (Jacques 2006). More specifically, the possibility of an internationally binding treaty to curb greenhouse gas emissions is viewed as a direct threat to sustained economic growth, the spread of free markets, the maintenance of national sovereignty, and the continued abolition of governmental regulations—key goals of conservatives (Oreskes and Conway 2010).…”
Section: Political Dynamics Of Climate Change In the American Publicmentioning
confidence: 99%
See 1 more Smart Citation
“…''Environmental skepticism'' is a subject position that operates in the arena of environmental regulation and politics in the United States (Jacques, 2006;Jacques et al, 2008;Jacques, 2008;Jacques, 2009;McCright and Dunlap, 2010;Jenkins, 2011). Environmental skeptics reject the authenticity of ecological problems, particularly those at the global scale, and further deny that ecological problems threaten modern civilization, a view reflected in Lomborg's The Skeptical Environmentalist (2001).…”
Section: Environmentality and Environmental Skepticismmentioning
confidence: 99%
“…Asked whether they believed it to have been ''proven beyond a reasonable doubt that the Earth is warming because of man-made pollution,'' only 23% of Republicans answered in the affirmative, by contrast to 98% of the Democrats. 4 Yet other evidence of the continued impact of contrarian arguments can be found in a 2003 Congressional report prepared for Congressman Henry Waxman, 5 a 2004 report by the Union of Concerned Scientists, 6 books such as Chris Mooney's Republican War on Science (2005) and popular magazines such as Newsweek (Begley, 2007), and in scholars' analyses in academic journals (e.g., Jacques, 2006;Krosnick et al, 2006;Leiserowitz, 2006;McCright and Dunlap, 2003;Oreskes, 2005). A 2005 peerreviewed study of US media coverage (Antilla, 2005) identified a large amount of articles which framed climate change in terms of debate, controversy, or uncertainty.…”
Section: Introductionmentioning
confidence: 99%